2012
DOI: 10.1155/2012/596846
|View full text |Cite
|
Sign up to set email alerts
|

Archaea in Symbioses

Abstract: During the last few years, the analysis of microbial diversity in various habitats greatly increased our knowledge on the kingdom Archaea. At the same time, we became aware of the multiple ways in which Archaea may interact with each other and with organisms of other kingdoms. The large group of euryarchaeal methanogens and their methane oxidizing relatives, in particular, take part in essential steps of the global methane cycle. Both of these processes, which are in reverse to each other, are partially conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 136 publications
0
28
0
1
Order By: Relevance
“…It has been suggested that the occurrence of methanogens is possible in anaerobic niches of gut habitats, where methanogens can be hosted as commensals participating in nutrient decomposition (Wrede et al. ), as is the case for Methanobrevibacter smithii which dominates the archaeal assemblage of the human gut (Eckburg et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the occurrence of methanogens is possible in anaerobic niches of gut habitats, where methanogens can be hosted as commensals participating in nutrient decomposition (Wrede et al. ), as is the case for Methanobrevibacter smithii which dominates the archaeal assemblage of the human gut (Eckburg et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The types of interactions between microbes can be complex and range from competitive to cooperative, syntrophic, even reaching obligate codependence (Hibbing et al, 2010;Moissl-Eichinger and Huber, 2011;Wrede et al, 2012;Morris et al, 2013). Holistic studies of such interspecies relationships are limited by difficulties in identifying and stably maintaining symbiotic microbial systems in the laboratory (Orphan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Two important projects—the Human Microbiome Project (HMP) [3] and the European Metagenomics of the Human Intestinal Tract (MetaHIT) Project [4]—have analyzed human-associated microbial communities and their genes (the microbiome ). The human microbiota, which has coevolved with the host, comprises mainly bacteria but also harbors other microbes, including fungi [5,6], viruses [7,8], archaea [9], and protozoa. Although the majority of commensals reside in the gastrointestinal tract, distinct microbial communities occupy other parts of the body, including the oral cavity [10,11], respiratory tract [12], and urogenital tract [13,14].…”
Section: Introductionmentioning
confidence: 99%